Effect of crack tip shape on near-tip deformation and fields in plastically compressible solids - Alam M.I.; Khan D.; Mittal Y.; Kumar S. (My University, 2025)
In the present study, the crack tip shape effect on near-tip deformation and fields is numerically investigated for a mode I crack under plane strain and small-scale yielding conditions. We explore here the quasi-static deformations of solids characterized by finite strain elastic–viscoplastic material model with bilinear hardening and hardening–softening–hardening hardness functions. For comparative analyses, both plastically incompressible and plastically compressible solids have been considered. It has been observed that the crack tip shape can have great consequence on the near-tip deformation and plastic fields. As the crack tip radius is increased, the plastic strain and stresses advance more to the tip of a crack as compared to the crack surface. It has also been revealed that the combination of crack tip curvature radius, material softening and plastic compressibility provides some useful and fundamental information for the near-tip deformation and plastic fields. © 2019, The Brazilian Society of Mechanical Sciences and Engineering.